Theodor W. Adorno's homecoming. (August 2016) - Bielsa, Esperança
Theodor Adorno has often been portrayed as the prototypical example of the permanent exile, even though, after living fifteen years in Britain and the US, he returned to Germany in 1949 and spent the last twenty years of his life there. This article traces Adorno's reflections on his homecoming and analyses how his experiences of exile and return shaped his mature thought. Conceiving homecoming not simply as a return to one's origins but as a continuation of a radical experience of the foreign, it builds on the remarkable continuity of Adorno's theory of intellectual experience over time. The article also explores homecoming in relation to Adorno's thought on language and translation, an aspect that has been little studied in the existing literature, both in terms of the articulation of a philosophy of language where the foreign plays an important role, and in terms of how language and translation were directly connected with Adorno's return.